ETIKA DALAM PANDANGAN IBN KHALDUN - Mohamad Iqbal Paudi (JOURNAL SCIENTIFIC OF MANDALIKA (JSM), 2022)
Ibn Khaldun was a leading Muslim scholar in his time. We can read the level of knowledge and examine the works he has written which are still the main reading material in various scientific aspects. A life full of political intrigue made him learn a lot from the matter of moral and ethical power. He is a scholar who is so obedient to Islam, this can be seen from his thoughts which become Islamic law in this case the Qur'an and Hadith as hujjah arguments, as well as his thoughts on ethics. This study aims to see the relevance of Ibn Khaldun's ethical view as a special view. This research is a library research (Library Research). The data collection of this research is by doing documentation, then data analysis by using descriptive-analytic method. The results of this study are, according to Ibn Khaldun, religion is the main source of ethics, religion through its teachings and laws teaches humans about noble moral values ​​such as fairness, honesty, and so on. The teachings of the morality of the hadith religion in all aspects of life such as political economy and education, all of which are basically aimed at creating a good life.